Hilbert Space Decomposition Properties of Complex Functions and Their Applications (Contemporary Mathematics, 2023)
We analyzed the classical problem of decomposing the Hilbert space of holomorphic functions, especially their splitting into the product or sum of domain-separated components. For the Bergman space of analytical functions, we obtained a special decomposition satisfying the assigned growth degree properties. Concerning a general Hilbert space of analytical functions on a connected domain, we studied its α-invariant decomposition and related ergodic consequences. As an interesting consequence, we obtained the decomposition theorem for an ergodic α-mapping on the Bergman space of holomorphic functions.
Keywords: decomposition; Bergman space; Hilbert space decomposition; Wold decomposition; invariant mapping; space invariance; ergodicity